2021
DOI: 10.1038/s41586-021-03681-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of Ad26.COV2.S vaccine against SARS-CoV-2 variants in humans

Abstract: The Ad26.COV2.S vaccine [1][2][3] has demonstrated clinical efficacy against symptomatic COVID-19, including against the B.1.351 variant that is partially resistant to neutralizing antibodies 1 . However, the immunogenicity of this vaccine in humans against SARS-CoV-2 variants of concern remains unclear. Here we report humoral and cellular immune responses from 20 Ad26.COV2.S vaccinated individuals from the COV1001 phase 1/2 clinical trial 2 against the original SARS-CoV-2 strain WA1/2020 as well as against th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

24
232
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 318 publications
(265 citation statements)
references
References 24 publications
24
232
7
2
Order By: Relevance
“…More interestingly, rsFC between ACC and pre-and postcentral gyrus was positively correlated with the unpleasantness ratings in response to the pain stimulation in both high and low distraction conditions in the two groups of participants. Supporting our results, several studies have shown a strong relationship between rsFC of ACC and pain perception in healthy young subjects (Boly et al, 2007;Proverbio et al, 2009;Ploner et al, 2010) and in diseases such as Alzheimer's (Beach et al, 2017). Furthermore, it seems that baseline fluctuations in ACC activity could be related to fluctuations in the subjective perception of identical nociceptive stimuli (Boly et al, 2007) and could predict individual pain thresholds (Spisak et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…More interestingly, rsFC between ACC and pre-and postcentral gyrus was positively correlated with the unpleasantness ratings in response to the pain stimulation in both high and low distraction conditions in the two groups of participants. Supporting our results, several studies have shown a strong relationship between rsFC of ACC and pain perception in healthy young subjects (Boly et al, 2007;Proverbio et al, 2009;Ploner et al, 2010) and in diseases such as Alzheimer's (Beach et al, 2017). Furthermore, it seems that baseline fluctuations in ACC activity could be related to fluctuations in the subjective perception of identical nociceptive stimuli (Boly et al, 2007) and could predict individual pain thresholds (Spisak et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, resting-state functional networks, such as the default mode network (DMN) and the salience network, are altered in both healthy older individuals (Tomasi and Volkow, 2012;Huang et al, 2015) and chronic pain patients (Napadow et al, 2010;Kucyi and Davis, 2015;Martucci and Mackey, 2016). In this sense, it is well known that there is a strong relationship between resting-state functional connectivity (rsFC) of several brain areas belonging to these networks [i.e., anterior cingulate cortex (ACC), insula and amygdala] and pain perception in healthy young subjects (Proverbio et al, 2009;Ploner et al, 2010), as well as in patients with aging-related diseases such as Alzheimer's disease (Beach et al, 2017). Thus, for instance, it has been shown that ACC baseline fluctuations positively correlate with pain intensity ratings after nociceptive stimulation in a healthy population (Boly et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data reported here differ somewhat from those reported by Jongeneelen et al who found that Ad26.COV2.S-elicited antibody titers were mostly maintained against the variants 20 . In addition, Alter et al reported a 5-fold decrease in neutralizing antibody titer against Beta and 3.3-fold decrease against the Gamma variant by the sera from Ad26.COV2.S vaccination 21 which were less pronounced than those reported here. While the studies used similar assays to measure antibody neutralization and analyzed sera collected at a similar time-point post-immunization, it is possible that differences in the study populations accounted for the experimental differences.…”
Section: Discussioncontrasting
confidence: 78%
“…Overall, these evidences support the concept that a single-dose of an adenoviral vaccine, which is cheap and easy to deploy in a pandemic setting, represents a good tool to effectively prime the immune system, which can be boosted afterwards by a single dose of a different vaccine platform, reaching high levels of immune responses. As preclinical and clinical evidence suggest 6,9 , keeping adenoviral vectored vaccines as part of heterologous vaccination regimens may be the key for optimal induction and persistence of T cell responses, a feature that may confer cross-protection in the context of already circulating and newly emerging SARS-CoV-2 variants 10 . Further prospective and controlled investigations are mandatory to confirm these data and to evaluate the impact of age and the optimal timing between prime and boost as well as the order of administration of the heterologous vaccines.…”
mentioning
confidence: 99%